2019
DOI: 10.1002/cctc.201901579
|View full text |Cite
|
Sign up to set email alerts
|

Defects Engineering in Photocatalytic Water Splitting Materials

Abstract: Defect engineering has been proved to be an effective approach to improve the photocatalytic performance of the photocatalysts. In this review, recent progress in the design of the defects with the classified anion vacancies, cation vacancies, and multi-vacancies on the photocatalysts to promote the photocatalytic activity is summarized. The strategies to manu-facture the defective photocatalysts and the characterization techniques to distinguish various defects are presented. The roles of defects in photocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 98 publications
1
90
0
Order By: Relevance
“…[ 40 ] Fine‐tuning of defective surface exhibits a prominent modulation in geometries, electronic properties, atomic coordination and charge separation of nanomaterials, which substantially interferes the catalytic and reactive performance. [ 41,42 ] Profiting from these features, the intentional engineering of surface vacancies has held enormous passion in energy harvest and conversion. However, the creation of desirable vacancies is complicated as the introduction of surface deficiency tends to induce the unexpected bulk defects, which is detrimental to the photocatalysts, especially in promoting the photoexcited charge recombination during photocatalysis.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[ 40 ] Fine‐tuning of defective surface exhibits a prominent modulation in geometries, electronic properties, atomic coordination and charge separation of nanomaterials, which substantially interferes the catalytic and reactive performance. [ 41,42 ] Profiting from these features, the intentional engineering of surface vacancies has held enormous passion in energy harvest and conversion. However, the creation of desirable vacancies is complicated as the introduction of surface deficiency tends to induce the unexpected bulk defects, which is detrimental to the photocatalysts, especially in promoting the photoexcited charge recombination during photocatalysis.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…However, if the charge carriers cannot transfer rapidly due to intrinsic electrical conductivity limitations of the materials, the excitons relax to the ground state and generate heat or light (Figure 1(iii)). Additionally, charge carriers can be trapped in trap states, such as antisites, interstitials, and vacancy defects (Figure 1 (iv)) [5][6][7][8][9]. The surface contains a high density of vacancy defects because the bulk crystalline structure does not elongate further.…”
Section: Photogenerated Charge Carriers Dynamicsmentioning
confidence: 99%
“…The surface chemical structure of materials has different chemical and electronic properties from the bulk crystalline structure, which generates charged dangling bonds, various coordination states, and different chemical potential. The charged dangling bonds on the surface induce a surface dipole, and induce the Fermi level shift at the surface to produce a built-in potential [7,8]. Also, the facets of the surface have distinctive atomic arrangements, and coordination states, and possess the different chemical and electronic properties.…”
Section: Surface States At the Solid-liquid Interface For Charge Tranmentioning
confidence: 99%
“…HRTEM image also revealed that a disordered layer appeared around NiO due to the existence of oxygen vacancy. [ 45–47 ] The corresponding elemental mappings of partial SEM image revealed the NiTCPP molecule was homogeneously loaded on the surface of NiO (Figure 1f). To further confirm the integrated system has been successfully prepared, UV–visible diffuse reflectance spectra (DRS) were performed and displayed in Figure 1g.…”
Section: Figurementioning
confidence: 99%
“…In addition, electron spin resonance (ESR) spectroscopy can provide the information of the unpaired electrons and the relative concentration of defect can be obtained according to different g values and intensities. [ 46 ] As shown in Figure S5 (Supporting Information), the ESR signal observed in different NiO samples with g = 2.001 can be assigned to oxygen vacancy. [ 56 ] The signal intensity increased with the increased calcination temperature, meaning much more oxygen vacancies were introduced.…”
Section: Figurementioning
confidence: 99%